Prinzmetal Angina: ECG Changes and Clinical Considerations: A Consensus Paper - de Luna, Antonio Bayés (Ann Noninvasive Electrocardiol, 2014)
BACKGROUND: We will focus our attention in this article in the ECG changes of classical Prinzmetal angina that occur during occlusive proximal coronary spasm usually in patients with normal or noncritical coronary stenosis. RESULTS: The most important ECG change during a focal proximal coronary spasm is in around 50% of cases the appearance of peaked and symmetrical T wave that is followed, if the spasm persist, by progressive ST‐segment elevation that last for a few minutes, and later progressively resolve. The most frequent ECG changes associated with ST‐segment elevation are: (a) increased height of the R wave, (b) coincident S‐wave diminution, (c) upsloping TQ in many cases, and (d) alternans of the elevated ST‐segment and negative T wave deepness in 20% of cases. The presence of arrhythmias is very frequent during Prinzmetal angina crises, especially ventricular arrhythmias. The prevalence and importance of ventricular arrhythmias were related to: (a) duration of episodes, (b) degree of ST‐segment elevation, (c) presence of ST–T wave alternans, and (d) the presence of >25% increase of the R wave. CONCLUSIONS: The incidence of Prinzmetal angina is much lower then 50 years ago for many reasons including treatment with calcium channel blocks to treat hypertension and ischemia heart disease and the decrease of smoking habits.